2016
DOI: 10.1259/bjr.20160109
|View full text |Cite
|
Sign up to set email alerts
|

Value of 18F-FDG heterogeneity for discerning metastatic from benign lymph nodes in nasopharyngeal carcinoma patients with suspected recurrence

Abstract: Objective: This study investigated the value of fluorine-18 fludeoxyglucose ( 18 F-FDG) heterogeneity as an indicator of metastatic lymph nodes (LNs) in patients with nasopharyngeal carcinoma (NPC). We further assessed whether addition of this parameter improves diagnostic performance beyond that provided by maximum standardized uptake value (SUV max ). Methods: We analyzed 74 LNs that were suspicious for metastasis. These LNs were measured for coefficient of variation (CV) of 18 F-FDG uptake, which was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Different cell groups in malignant tumors could have different behaviors and treatment responses, and the heterogeneity of malignant tumors is related to oxygen consumption and glucose metabolism (28). Previous studies have demonstrated that heterogeneous parameters, such as HI and COV in 18 F-FDG PET imaging, could benefit treatment response evaluation and patient outcomes in nonsmall cell lung cancer, rectal carcinoma, and nasopharyngeal carcinoma (29)(30)(31). The findings of the present study confirm the potential of these intratumoral heterogeneous semi-quantitative parameters after lesion delineation procedures based on static 18 F-FET PET/CT imaging, which could also contribute to the further understanding of glioma heterogeneity mechanisms in amino acid tracer imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Different cell groups in malignant tumors could have different behaviors and treatment responses, and the heterogeneity of malignant tumors is related to oxygen consumption and glucose metabolism (28). Previous studies have demonstrated that heterogeneous parameters, such as HI and COV in 18 F-FDG PET imaging, could benefit treatment response evaluation and patient outcomes in nonsmall cell lung cancer, rectal carcinoma, and nasopharyngeal carcinoma (29)(30)(31). The findings of the present study confirm the potential of these intratumoral heterogeneous semi-quantitative parameters after lesion delineation procedures based on static 18 F-FET PET/CT imaging, which could also contribute to the further understanding of glioma heterogeneity mechanisms in amino acid tracer imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies are using pretreatment MRI features, which have been used to predict progression-free survival in stage III-IVb patients [63][64][65] and in a smaller sample including low grade tumors [66]. A few earlier studies tried to measure FDG uptake heterogeneity by using different quantitative measures, including SUVmax/SUVmean [67], SUV standard deviation/SUVmean [68] and the derivative of the volume-threshold function [69]; however, a more recent study [13] using the radiomics approach found skewness (a first-order feature) to be a predictor of relapse-free survival and uniformity (a texture feature) to be a predictor of overall survival, which improved the prognostic stratification of other risk factors found by using multivariate analysis, namely age and serum EBV DNA load. A large multicenter study recently showed that treatment decision and prognosis for specific stages could reliably based on a radiomic based nomogram [70].…”
Section: Nasopharyngeal Carcinomamentioning
confidence: 99%